PSYCHOLOGICAL STRESS IN LEARNING ENGLISH AND ITS EFFECTIVE SOLUTIONS (Ustozlar uchun, 2026)
This article analyzes psychological stress in the process of learning English, its causes, and effective solutions. The study focuses on factors such as lack of confidence, fear of making mistakes, perfectionism, social comparison, and external pressure. It also provides scientifically based recommendations to improve language learning efficiency and reduce psychological stress.